Smart Home Wireless System - Md Asran, Muhammad Akmal; Abdul Sukor, Jumadi (Progress in Engineering Application and Technology, 2021)
The purpose of this project is to produce a Smart Home Wireless System prototype that has the advantage of maintaining home security by provide the facilities such as turning on and off the lights without having to use the switch and know the lighting conditions. In this project, there are 2 important parts to ensure this prototype is complete, namely software and hardware. For the hardware part, this prototype project uses Node Mcu ESP8266, relays, LDR sensor and LED bulb where all the hardware will be connected to the main processing unit known as Arduino. The use of LDR sensor as a light detector is to know the condition of the lamp used is in good condition or not. In addition, the relay is used to allow and turn off the electric current that will be connected to the LED lights available on the circuit of this project according to the instructions process from the Arduino Uno as a microcontroller. Furthermore, the use of Node Mcu ESP8266 is component to connect between project devices and smartphones using Wi-Fi wireless technology. The software used in this prototype is Arduino Ide to construction of command for Arduino Uno and Node Mcu ESP8266. Blynk application is to construction for the user interface available on smartphones. Users who are outside the home or work area will get info from their smartphone in real-time.